Atrial fibrillation burden and the risks of ischemic stroke and intracranial hemorrhage: comparisons of catheter ablation, medical therapy, and non-atrial fibrillation population. (25th November 2020) - Kim, M; Yu, H.-T; Kim, T.-H; Uhm, J.-S; Seung, J.-H; Joung, B.-Y; Lee, M.-H; Pak, H.-N
Abstract: Background: Although atrial fibrillation (AF) burden was known to be related to the risk of ischemic stroke (IS), clinical evidence regarding intracranial hemorrhage (ICH) or comparison of the patients after AF catheter ablation (AFCA) and the non-AF population are limited. Objective: We explored the risks of IS and ICH after AFCA or medical therapy (Med) in the AF population and the matched non-AF population. Methods: We compared 1, 629 with AFCA (Yonsei AF cohort), 3, 258 with Med (Korean National Health Insurance Sharing Service [KNHISS] database), and 3, 258 non-AF population (KNHISS database) after 1:2:2 propensity-score match in terms of clinical characteristics and medications (57±12 years old, 22.1% female). IS and ICH were determined by ICD code, brain imaging, and hospital admission in Med and non-AF groups. All AFCA patients underwent regular rhythm follow-up, and the medications including antithrombotic therapies were evaluated for 52±23 months. Results: 1. Among AFCA group, the annualized IS rate was significantly higher in the patients with sustaining recurrence of AF/atrial tachycardia (AT) after the last ablation procedure than those remaining in sinus rhythm (SR) (0.87% vs. 0.24%, p=0.017; HR 4.87 [1.36–17.49], p=0.015; log rank p=0.003). 2. The annualized ICH rate was 0% in SR group and 0.06% in sustaining recurrent AF/AT group after AFCA (p=0.361, log rank p=0.545). 3. The annualized IS rate was significantly higher in Med group (1.09%) than in AFCA group (0.30%, p<0.001, log rank p<0.001) or non-AF group (0.34%, p<0.001, log rank p<0.001). There was no significant difference in annualized IS rate between AFCA and non-AF groups (p=0.673, log rank p=0.874) 4. The annualized ICH rates were 0.17% in Med group, 0.06% AFCA group (p=0.023, log rank p=0.042 vs. Med; p=0.172, log rank p=0.193 vs. non-AF), and 0.12% in non-AF group (p=0.226, log rank p=0.241 vs. Med), respectively. Conclusion: Post-procedural AF burden influence the risk of IS. AFCA significantly reduces the risks of both IS and ICH to the extent of non-AF population compared to Med group. Funding Acknowledgement: Type of funding source: None